2017
DOI: 10.3382/ps/pex141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multi-carbohydrase and phytase on standardized ileal digestibility of amino acids and apparent metabolizable energy in canola meal fed to broiler chicks

Abstract: Two assays were conducted to evaluate nutritive value of canola meal (CM) fed to broiler chicks without or with a multi-carbohydrase (MC) preparation (700 U α-galactosidase, 2,200 U galactomannanase, 30,000 U xylanase, and 22,000 U β-glucanase per kg of diet) and phytase (Phy, 500 FTU per kg of diet). Assay 1 determined apparent total tract digestibility (ATTD) of nutrients and metabolizable energy (AME) by the difference method. Assay 2 determined apparent ileal digestibility (AID) and standardized ileal dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
3
11
1
1
Order By: Relevance
“…The MC and Phy increased (P < 0.05) the AME n of WB by 9.76% and 5.14%, respectively, compared with WB without enzymes. Present observations are in agreement with Gallardo et al (2017) who reported that birds fed with canola meal plus Phy-MC combination showed higher energy retention compared with control diet and diets with alone enzymes. Selle et al (2009) reported that broilers fed a Phy-xylanase wheatbased diet showed an increase AME n of 0.63 MJ/ kg on a DM basis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The MC and Phy increased (P < 0.05) the AME n of WB by 9.76% and 5.14%, respectively, compared with WB without enzymes. Present observations are in agreement with Gallardo et al (2017) who reported that birds fed with canola meal plus Phy-MC combination showed higher energy retention compared with control diet and diets with alone enzymes. Selle et al (2009) reported that broilers fed a Phy-xylanase wheatbased diet showed an increase AME n of 0.63 MJ/ kg on a DM basis.…”
Section: Discussionsupporting
confidence: 93%
“…The present results indicate that AA digestibility was improved in the broilers when fed with WB diets supplemented with exogenous enzymes. Thus, there were beneficial effects of enzymes on N retention increasing the absorption of AA (Dadalt et al, 2017;Gallardo et al, 2017). The MC and Phy combination showed a higher effect on AA digestibility in the SID of Arg, His, Leu, Lys, Phe, Thr, Val, Asp, Cys, Glu, and Ser.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, during Lactobacillus acidophilus fermentation of rapeseed meal, a considerable amount of amylases, proteases, phytases, and β -glucanases may be produced and activated. These enzymes consumed the insoluble fibers in RSM and produced soluble matters with simple structure; carbohydrate composition was modified as a result of microbial metabolism and, to some extent, due to activation of inherent enzymes in the cereal protein feedstuff [ 43 ]. In a study by Alahyarishahrasb et al [ 29 ], enzyme treatment ( β -glucanase, 0.5 g/kg) barley had significantly higher AMEn values than no enzyme treatment when fed to cockerels.…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Cowieson and Ravindran [ 49 ], the increased protein digestibility by phytase supplementation was associated with the reduction of endogenous protein flow and nutrition losses. Gallardo et al [ 43 ] also noticed the reduced phytate decreased the endogenous inputs for protein digestion, which resulted in an improvement in SID of amino acids, principally Thr, Asp, and Gly, which predominate in the endogenous proteins [ 52 ]. This may be the same way FRSM achieved higher AID and SID of Ala, Val, Ile, Leu, Tyr, Lys, Arg, and Phe observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, investigations attesting to a positive effect of proteases on the energy values of diets are more common (Olukosi et al 2015;Mahmood et al 2017). Gallardo et al (2017) evaluated the addition of a complex composed of carbohydrase and protease to diets with maize distillers' dried grain with solubles and observed an increase of AMEn, suggesting that the presence of protease improves the digestion of nutrients in the birds' gut. On the other hand, Scotta et al (2016) found that the addition of a meal containing α-amylase from maize residues had a significant effect on the values of AME and AMEn, and there was a positive effect on the coefficient of metabolizable energy.…”
Section: Resultsmentioning
confidence: 99%